PROJECT-BASED LEARNING IN THE LANGUAGE CLASSROOM: ENGAGING LEARNERS IN AUTHENTIC LANGUAGE USE - Hamidah, Fitria Nur; Pinkan, Friska Nabilla (Transpublika Publisher, 2022)
Project-based learning is a valuable instructional approach that can promote the simultaneous development of language, content, and skills in academic EFL classrooms. By enabling students to engage in real-world projects, this approach not only transforms the dynamics of the classroom but also empowers learners to take ownership of their learning experiences, ultimately fostering higher levels of academic literacy and critical thinking skills in language acquisition. This study explored the impact of project-based learning on language skills and academic performance in ESL classrooms. The researchers used a combination of classroom observations, student surveys, and work sample analysis. The findings show that project-based learning significantly improved students' language proficiency, critical thinking, and engagement. Students reported being more motivated and having a deeper understanding of the language, as they could apply their knowledge to real-world situations.